Osmotic-stress-induced synthesis and degradation of inorganic polyphosphates in the alga phaeodactylum- tricornutum - Leitão, J. M. (2015)
The potential role of inorganic polyphosphates in the response of algal cells to osmotic stress was investigated. We show that changes in polyphosphate metabolism of algae induced by osmotic stress can be easily determined by measuring the metachromatic shift of toluidine blue produced by polyphosphate and by analysing the size of the extracted polyphosphate on urea/polyacrylamide gels. The amount and size of polyphosphate were found to differ considerably among different algal species. It is demonstrated that the alga Phaeodactylum tricornutum responds to hyperosmotic stress with a marked elongation of polyphosphate molecules and a decrease in the total amount of extractable polyphosphate, while exposure to hypoosmotic stress results in an increase in soluble shorter-chain polyphosphates and a rise in total polyphosphate content.